2004
DOI: 10.1021/la035777v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Nanocrystalline TiO2 with Lower Band Gap Showing High Photocatalytic Activity

Abstract: Nanocrystalline TiO2 was synthesized by the solution combustion method using titanyl nitrate and various fuels such as glycine, hexamethylenetetramine, and oxalyldihydrazide. These catalysts are active under visible light, have optical absorption wavelengths below 600 nm, and show superior photocatalytic activity for the degradation of methylene blue and phenol under UV and solar conditions compared to commercial TiO2, Degussa P-25. The higher photocatalytic activity is attributed to the structure of the catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
312
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(353 citation statements)
references
References 28 publications
25
312
1
3
Order By: Relevance
“…Another issue is the process of creation of hole-electron pairs over Pt/TiO 2 catalysts. The energy gap of TiO 2 is 3.2 eV (anatase), which allows the electron to be transferred from the valence band to the conduction band under UV [35]. It was earlier mentioned that in the case of the light used in this work, UV constitutes only a few percent of the total radiation.…”
Section: The Activity Tests and Overall Discussionmentioning
confidence: 96%
“…Another issue is the process of creation of hole-electron pairs over Pt/TiO 2 catalysts. The energy gap of TiO 2 is 3.2 eV (anatase), which allows the electron to be transferred from the valence band to the conduction band under UV [35]. It was earlier mentioned that in the case of the light used in this work, UV constitutes only a few percent of the total radiation.…”
Section: The Activity Tests and Overall Discussionmentioning
confidence: 96%
“…However, doping inevitably affects the semiconducting properties of materials, which may be disadvantageous to the photocatalytic performance. Alternatively, as discussed subsequently, doping also may act advantageously through reduction in the band gap and improvement in the charge carrier separation and associated extended exciton lifetime [18,68,73,151].…”
Section: Rutile-anatase Mixturesmentioning
confidence: 99%
“…• Reduction of the band gap in titania [18,151] • Introduction of mid-gap states [56,163] • Improvement in charge carrier separation [68,73] • Increase in the levels of surface-adsorbed species (e.g., hydroxyl radicals) [43] It often is not appreciated that all titania is contaminated with some levels of impurities. The presence of unintentional impurities or intentional dopants has a strong effect on the kinetics of the anatase to rutile transition [170].…”
Section: Dopant Effectsmentioning
confidence: 99%
“…Previous studies showed that anatase phase of titania has a higher photocatalytic activity than rutile phase and it can be attributed to the presence of a higher degree of surface hydroxyl groups. 29,30 Though the shape-controlled synthesis of TiO2 and RuXTi1-XO2 resulted in anatase and rutile type phases, the significantly higher concentration of anatase type revealed that surface hydroxyl group catalyzed photocatalytic degradation mechanism proposed by Nagaveni et al 30 is quite valid in the present systems. However, higher degradation rate exhibited by RuXTi1-XO2 UV-VISIBLE LIGHT RESPONSIVE RUTHENIUM DOPED TITANIA Ashwini Ashok et al…”
Section: Resultsmentioning
confidence: 72%